The Risk and Return of Human Capital Investments - Kristian Koerselman; Roope Uusitalo (Institute for the Study of Labor (IZA), 2013)
Investing in human capital increases lifetime income, but these investments may involve substantial risk. In this paper we use a Finnish panel spanning 22 years to predict the mean, the variance and the skew of the present value of lifetime income, and to calculate certainty equivalent lifetime income at different levels of education. We find that university education is associated with about a half a million euro increase in discounted lifetime disposable income compared to vocational high school. Accounting for risk does little to change this picture. By contrast, vocational high school is associated with only moderately higher lifetime income compared to compulsory education, and the entire difference is due to differential nonemployment.
Keywords: C33; I24; J31; 330; lifetime income; risk; education; human capital